Low Phenotypic Penetrance and Technological Impact of Yeast [GAR+] Prion-Like Elements on Winemaking - Gonzalez, Ramon; Tronchoni, Jordi; Mencher, Ana; Curiel, José Antonio; Rodrigues, Alda Joao; López-Berges, Laura; Juez, Cristina; Patil, Kiran Raosaheb; Jouhten, Paula; Gallego, Noelia; Omarini, Alejandra; Fernández-Preisegger, Mariana; et al. (Frontiers in Microbiology, 2019)
[GAR+] prion-like elements partially relieve carbon catabolite repression in Saccharomyces cerevisiae. They have been hypothesized to contribute to wine yeast survival and alcohol level reduction, as well as communication with bacteria and stuck fermentation. In this work, we selected [GAR+] derivatives from several genetic backgrounds. They were characterized for phenotypic penetrance, heritability and confirmed as prion-like through curing by desiccation. In terms of fermentation kinetics, the impact of the prion on anaerobic wine fermentation (natural grape juice) was either neutral or negative, depending on the genetic background. Likewise, residual sugars were higher or similar for [GAR+] as compared to the cognate [gar-] strains. The prions had little or no impact on glycerol and ethanol yields; while acetic acid yields experienced the highest variations between [GAR+] and [gar-] strains. Strains analyzed under aerobic conditions followed the same pattern, with either little or no impact on fermentation kinetics, ethanol or glycerol yield; and a clearer influence on volatile acidity. Although no clear winemaking advantages were found for [GAR+] strains in this work, they might eventually show interest for some combinations of genetic background or winemaking conditions, e.g. for reducing acetic acid yield under aerated fermentation.